The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.4149/bll_2019_076
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of neutrophil-to-lymphocyte ratio and hematologic parameters in patients with Graves’ disease

Abstract: AIM: While the ratio of neutrophil-to-lymphocyte (NLR) increases with infl ammation, its importance in Graves' disease is not clear. The aim of this study was to evaluate NLR, a marker of chronic infl ammmation, in Graves' disease. METHODS: 86 Graves' patients (37 before treatment,49 euthyroid patients after treatment) and 112 controls were enrolled. Hematologic parameters, thyroid function tests, age and gender were recorded. NLRs were calculated. Firstly, groups were composed as Graves' group (Group1) and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
5
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 18 publications
2
15
5
2
Order By: Relevance
“…In accordance to previous data, we proved that there were no statistically significant differences in basophil and eosinophil counts in GD patients with and without GO compared to controls [ 44 , 48 ]. Some reports suggested increased percentage of eosinophil in peripheral blood in GD patients compared to healthy individuals, but it might be associated with concomitant Th-2-predominant disorders [ 48 , 49 , 50 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In accordance to previous data, we proved that there were no statistically significant differences in basophil and eosinophil counts in GD patients with and without GO compared to controls [ 44 , 48 ]. Some reports suggested increased percentage of eosinophil in peripheral blood in GD patients compared to healthy individuals, but it might be associated with concomitant Th-2-predominant disorders [ 48 , 49 , 50 ].…”
Section: Discussionsupporting
confidence: 92%
“…What is more, it was observed that activated T cells release cytokines, such as tumor necrosis factor α (TNF-α), interleukin 1 β (IL-1β), interleukin 6 (IL-6), and interleukin (IL-17), which results in the increased production and recruitment of neutrophils and macrophages. This hypothesis partially explains neutrophilia, increased monocyte counts, and MLR values in the course of GD which were observed in our research [ 5 , 12 , 28 , 29 , 44 , 46 ].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Even a quick and simple search in the literature reveals many examples of the use of PIBs to reflect the systemic status of both infection and inflammation and their use as a surrogate for a pathway to end-organ disease, mainly in the immunocompromised population, including cancer, PLWH and cirrhotic patients. [7][8][9][10] Recently, in a large cohort of unselected cancer patients, NLP was found to have a predictive value for recurrence and overall survival. 10 Evaluated together with the results of another study conducted in colorectal cancer patients, reflecting NLR as a systemic inflammatory response marker suitable to define the risk stratification of cancer patients, it is possible to consider PIBs as tumor-associated inflammatory response parameters in terms of relapses and recurrences in neoplastic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with diabetes, who are considered to have low-grade inflammation in vivo , show increased WBC, NE, and LY [ 16 ]. Patients with Graves' disease, a chronic autoimmune disease, have higher LY and Mo in blood [ 17 ]. Thus, WBC, NE, LY, and Mo can suggest the systemic inflammation in subjects without obvious infection.…”
Section: Methodsmentioning
confidence: 99%